Geochemistry of hydrothermal fluids from the eastern sector of the Sabatini Volcanic District (central Italy). (September 2017) - Cinti, D.; Tassi, F.; Procesi, M.; Brusca, L.; Cabassi, J.; Capecchiacci, F.; Delgado Huertas, A.; Galli, G.; Grassa, F.; Vaselli, O.; Voltattorni, N.
Abstract: This study reports a complete geochemical dataset of 215 water and 9 gas samples collected in 2015 from thermal and cold discharges located in the eastern sector of the Sabatini Volcanic District (SVD), Italy. Based on these data, two main aquifers were recognized, as follows: 1) a cold Ca-HCO3 to Ca(Na)-HCO3 aquifer related to a shallow circuit within Pliocene-Pleistocene volcanic and sedimentary formations and 2) a deep CO2 -pressurized aquifer hosted in Mesozoic carbonate-evaporitic rocks characterized by a Ca-HCO3 (SO4 ) to Na(Ca)-HCO3 (Cl) composition. A thick sequence of low-permeability formations represents a physical barrier between the two reservoirs. Interaction of the CO2 -rich gas phase with the shallow aquifer, locally producing high-TDS and low-pH cold waters, is controlled by fractures and faults related to buried horst-graben structures. The δ 18 O-H2 O and δD-H2 O values indicate meteoric water as the main source for both the shallow and deep reservoirs. Carbon dioxide, which is characterized by δ 13 C-CO2 values ranging from −4.7 to +1.0‰ V-PDB, is mostly produced by thermo-metamorphic decarbonation involving Mesozoic rock formations, masking possible CO2 contribution from mantle degassing. The relatively low R/Ra values (0.07–1.04) indicate dominant crustal He, with a minor mantle He contribution. The CO2 / 3 He ratios, up to 6 × 10 12, support a dominant crustal source for these two gases. The δ 34 S-H2 S values (from +9.3 to +11.3‰ V-CDT) suggests that H2 S is mainly related to thermogenic reduction of Triassic anhydrites. The δ 13 C-CH4 and δD-CH4 values (from −33.4 to −24.9‰ V-PDB and from −168 to −140‰ V-SMOW, respectively) and the relatively low C1 /C2+ ratios (<100) are indicative of a prevailing CH4 production through thermogenic degradation of organic matter. The low N2 /Ar and high N2 /He ratios, as well as the 40 Ar/ 36 Ar ratios (<305) close to atmospheric ratio, suggest that both N2 and Ar mostly derive from air. Notwithstanding, the positive δ 15 N-N2 values (from +0.91 to +3.7‰ NBS air) point to a significant extra-atmospheric N2 contribution. Gas geothermometry in the CH4 -CO2 -H2 and H2 S-CO2 -H2 systems indicate equilibrium temperatures <200 °C, i.e. lower than those measured in deep geothermal wells (∼300 °C), due to either an incomplete attainment of the chemical equilibria or secondary processes (dilution and/or scrubbing) affecting the chemistry of the uprising fluids. Although the highly saline Na-Cl fluids discharged from the explorative geothermal wells in the study area support the occurrence of a well-developed hydrothermal reservoir suitable for direct exploitation, the chemistry of the fluid discharges highlights that the uprising hydrothermal fluids are efficiently cooled and diluted by the meteoric water recharge from the nearby Apennine sedimentary belt. This explains the different chemical and isotopic features shown by the fluids from the eastern and western sectors of SVD, respectively, the latter being influenced by this process at a lesser extent. Direct uses may be considered a valid alternative for the exploitation of this resource. Highlights: A geochemical study was made for fluids in the eastern Sabatini Volcanic District. Waters emerge from both shallow (cold) and deep (thermal and CO2 -rich) reservoirs. Gas phase is dominated by CO2 which is mainly originated by decarbonation reactions. The structural framework plays a key role in the upraise of deep-originated fluid. Secondary processes significantly affect the chemistry of the uprising deep fluids.